Advances in free-piston internal combustion engines: A comprehensive review. (5th May 2021) - Guo, Chendong; Zuo, Zhengxing; Feng, Huihua; Roskilly, Tony
Highlights: Recent advances in various types of free-piston internal combustion engines are reviewed. Key challenges of free-piston internal combustion engines technology are summarized. Research trends of free-piston internal combustion engines are discussed. Abstract: Free-piston internal combustion engines (FPICEs) have many potential advantages, such as simple structure, high conversion efficiency, multi-fuel feasibility and multi-output power types, because their piston motion is not restricted by the crankshaft system. Therefore, FPICEs have received considerable attention worldwide for many decades. According to recent research, the typical types of FPICEs include free-piston internal combustion engine linear generator, hydraulic free-piston internal combustion engine, linear Joule engine generator, and miniature FPICEs. This paper mainly reviews recent advances in these types of FPICEs. Firstly, the early research progress of FPICEs is briefly introduced. After that, the recent advances in the typical types of FPICEs are reviewed in more detail. These included the operating principles, piston dynamic characteristics, performances and control strategies for different types of FPICEs. Finally, the research trends and future development of FPICEs are discussed. It is noted that there are numerous research prospects for each type of FPICE, including performance optimisation, development of appropriate control systems, and future application exploration.